2019
DOI: 10.1002/nafm.10279
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology and Distribution of an Invasive Apex Predator: Flathead Catfish in Subestuaries of the Chesapeake Bay, Virginia

Abstract: Native to the central United States, Flathead Catfish Pylodictus olivaris have invaded Atlantic coast rivers from Florida to Pennsylvania. They are now invasive in several subestuaries of the Chesapeake Bay, yet contemporary accounts of their distribution do not exist. Due to their piscivorous nature, Flathead Catfish could have deleterious impacts on native ichthyofauna, yet their feeding ecology has not been well described in these systems. We used a large-scale, stratified random sampling effort to describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 51 publications
(92 reference statements)
0
50
0
Order By: Relevance
“…James River Flathead Catfish are known to consume at-risk Alosa spp. as they migrate to and from their spawning grounds (Schmitt et al 2017(Schmitt et al , 2019a(Schmitt et al , 2019b, posing a threat to Alosa spp. conservation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…James River Flathead Catfish are known to consume at-risk Alosa spp. as they migrate to and from their spawning grounds (Schmitt et al 2017(Schmitt et al , 2019a(Schmitt et al , 2019b, posing a threat to Alosa spp. conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Burkhead et al (1980) reported Flathead Catfish entered the James River in 1965 when a holding pond was flooded at the Hog Island Wildlife Management Area releasing approximately 50 individuals. The James River now supports a Flathead Catfish population (Schmitt et al 2017(Schmitt et al , 2019a, in addition to an established and dense Blue Catfish population Fabrizio et al 2018;Hilling et al 2018;Schmitt et al 2019b). Flathead Catfish largely inhabit areas upstream of Hopewell, Virginia, whereas the range of Blue Catfish extends further downstream into more saline waters with higher overall densities in the system.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations